Local bank office ownership, deposit control, market structure, and economic growth - Collender, Robert N.; Shaffer, Sherrill (Journal of Banking & Finance, 2003)
This paper tests empirical associations between banking market structure, banking regulation, and subsequent growth rates in local real per capita personal income. Our findings suggest that out-of-market bank mergers or acquisitions need not, ceteris paribus, impair local economic growth, and may even have beneficial effects in rural markets with the possible exception of farm-dependent areas. These findings derive from empirical models that relate both short-run and long-run growth rates to geographic restrictions on bank activity, concentration in local banking markets, in-market versus out-of-market ownership of local bank offices, and in-market versus out-of-market control of local bank deposits.